Fetal Magnetic Resonance Imaging of Megacystis microcolon intestinal hypoperistalsis syndrome - Wirasasmita, Dewi Asih; Sachlan, Alexandra (Jurnal Prima Medika Sains, 2024)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHs) is a rare congenital anomaly, involve urinary tract and gastrointestinal tract. The prognosis is dismal, the death is caused by infection. In general the diagnosis is made based on ultrasonography (US) examination during the antenatal period due to the presence megacystis in the female fetus. Fetal Magnetic Resonance Imaging (MRI) has excellent tissue contrast can depict colon caliber and meconium distribution, hence definitive diagnosis can be established and useful for counseling and post natal management.